Direct oral anticoagulant use in hospitalized patients with atrial fibrillation across body mass index categories: design and rationale for a retrospective cohort study - Fahad Shaikh; Rochelle Wynne; Ronald L. Castelino; Sally C. Inglis; Patricia M. Davidson; Caleb Ferguson (SAGE Publishing, 2024)
Background: Atrial fibrillation (AF) and obesity are common conditions globally; yet, there remains suboptimal pharmacological management contributing to high rates of hospitalization in patients with AF. The altered pathophysiology of both obese and underweight individuals may influence the pharmacology of medications, including those used to manage AF. This, in turn, increases the risk of adverse events and impacts patient risk for stroke and rehospitalization. Despite the well-established complications of obesity, research investigating the relationship between obesity and AF is scant. Objectives: The primary aim of this study is to describe cardiovascular-related hospitalization in AF patients according to BMI categories. A secondary aim is to describe anticoagulant and antiarrhythmic prescribing practice patterns in patients with AF, according to the BMI category. Design: A retrospective, exploratory descriptive observational cohort study, using routinely collected electronic medical record data from five public hospitals within a single health district, with a population dominantly that is culturally and linguistically diverse, and has a low socioeconomic status. Methods and analysis: Data extraction will include a 24-month period (January 2017 to December 2018) with a 12-month follow-up. All adult (⩾18 years) patients at discharge diagnosed with AF, prescribed any oral anticoagulant and/or oral rate/rhythm control agent, will be eligible for inclusion. Ethics and dissemination: Ethics approval from the health district and the University of Wollongong has been granted. Findings will seek to demonstrate associations between management strategies and patient outcomes, as well as describe patterns of acute care management from prescribers. These data will be used to inform and generate hypotheses for large-scale studies examining the impact of body weight on anticoagulation prescribing at national and global scales.